COMBINATION OF GIVING BABY MASSAGE WITH CITRONELLA OIL FOR APPETITE DISORDERS IN TODDLERS AGED 12-24 MONTHS - Sumariati, Putu Ayu Eka; Widiastini, Luh Putu; Lestari, Ni Putu Yunita Sri; Adhiestiani, Ni Made Egar (Program Studi Kebidanan Fakultas Kedokteran Universitas Sebelas Maret, 2024)
Background: Appetite disorder was noted as one of the nutritional issue causation in toddlers. Pharmacological or non-pharmacological methods have been developed to overcome this problem. As non-pharmacological method, researchers attempted to solve the problem by using a combination of baby massage and citronella oil.Objectives: This study aimed to determine the effect of the combination of giving baby massage and citronella oil on appetite disorders in toddlers aged 12-24 months in the area of UPTD. Puskesmas Abiansemal I.Method: The current study performed by using Quasi-Experimental with Pre-test Post-test Non-equivalent Control Group Design. Approximately 44 toddlers were involved in this study using a purposive sampling method divided into 22 toddlers in each control and experiment group. The CEBQ (Child Eating Behavior Questionnaire) was used to collect the data containing of 35 questions. Wilcoxon and Mann-Whitney tests were used in data analysis.Result: This research proved that baby massage with citronella oil affect the appetite disorders significantly in toddler aged 12-24 months. Mann-Whitney test reveals that the average score in treatment group was higher than control group with p-value of 0.002 (p<0,05).Conclusion: It is expected that the findings may provide education about the importance of giving baby massages with a combination of citronella oil in toddlers to increase a toddler’s appetite due to the need optimal nutrition.